IMPLEMENTASI PERDA KOTA MEDAN NO. 10/2021 TERHADAP PEDAGANG ASONGAN DAN PENGELAP MOBIL PERSFEKTIF SOSIOLOGI HUKUM DAN SIYAAH DUSTURIYAH - Fadila Putri, Vina; Nas, Zulkifli (Qolamuna : Jurnal Studi Islam, 2026)
Medan City Regulation Number 10 of 2021 concerning Public Order and Peace is an effort by the local government to regulate public spaces, particularly regarding the activities of street vendors and car washers. However, its implementation still faces structural and cultural obstacles, such as low legal awareness and community economic factors. These problems indicate that public order issues are not only juridical but also social, thus requiring a legal sociology study to assess the effectiveness of the regulation and a siyasah industrial perspective to test its compliance with the principles of justice and public welfare. This research is a non-doctrinal legal research using an empirical (empirical juridical) approach that produces descriptive data through data collection techniques through observation, interviews, and documentation. The data sources obtained are primary and secondary data. Primary data was obtained directly from informants through interviews, namely Civil Service Police Unit (Satpol PP), street vendors, car washers, and motorists at the research location, while secondary data was obtained from relevant references, including fiqh siyasah books, books, and journals. The study results show that the implementation of Medan City Regulation No. 10 of 2021 regarding street vendors and car washers has not been effective. The main obstacles lie in uneven communication due to the mobility of targets and a rigid bureaucratic structure with strict SOPs that limit the actions of officers. Public legal awareness also remains low, characterized by limited understanding and situational compliance. From a siyasa industrial perspective, this policy aims to establish order and public welfare, but its implementation requires a balance between legal firmness and the protection of community economic rights. Keywords: Public Order and Tranquility, Policy Implementation, Siyasah Dusturiyah, Sociology of Law